2021
DOI: 10.3390/biomedicines9091274
|View full text |Cite
|
Sign up to set email alerts
|

B Cells and Autoantibodies in AIRE Deficiency

Abstract: Autoimmune polyendocrine syndrome type 1 (APS-1) is a rare but severe monogenetic autoimmune endocrine disease caused by failure of the Autoimmune Regulator (AIRE). AIRE regulates the negative selection of T cells in the thymus, and the main pathogenic mechanisms are believed to be T cell-mediated, but little is known about the role of B cells. Here, we give an overview of the role of B cells in thymic and peripheral tolerance in APS-1 patients and different AIRE-deficient mouse models. We also look closely in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 157 publications
(165 reference statements)
0
4
0
Order By: Relevance
“…Studies performed since 2006 have shown that almost all APS‐1 patients also produce auto‐Abs against type I IFNs from early childhood onward 38,39,89,90 . The detection of these auto‐Abs has even been developed as a diagnostic test for APS‐1 148,149 . About a third of patients with autosomal dominant (AD) APS‐1, caused by dominant‐negative AIRE variants and associated with milder autoimmunity, also develop auto‐Abs against IFN‐α and/or IFN‐ω 150–155 .…”
Section: Genetic Causes Of Auto‐abs Against Type I Ifnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies performed since 2006 have shown that almost all APS‐1 patients also produce auto‐Abs against type I IFNs from early childhood onward 38,39,89,90 . The detection of these auto‐Abs has even been developed as a diagnostic test for APS‐1 148,149 . About a third of patients with autosomal dominant (AD) APS‐1, caused by dominant‐negative AIRE variants and associated with milder autoimmunity, also develop auto‐Abs against IFN‐α and/or IFN‐ω 150–155 .…”
Section: Genetic Causes Of Auto‐abs Against Type I Ifnsmentioning
confidence: 99%
“…38,39,89,90 The detection of these auto-Abs has even been developed as a diagnostic test for APS-1. 148,149 About a third of patients with autosomal dominant (AD) APS-1, caused by dominant-negative AIRE variants and associated with milder autoimmunity, also develop auto-Abs against IFNα and/or IFNω. [150][151][152][153][154][155] Patients with thymoma, a thymic epithelial tumor, 156 frequently develop T-cell or Ab-mediated autoimmune disease (including late-onset myasthenia gravis, 157 and tissue-specific auto-Abs of the APS-1 spectrum [158][159][160] ).…”
Section: G Ene Ti CC Aus E Sofauto -Abs Ag Ain S T T Ype I Ifn Smentioning
confidence: 99%
“…Since AIRE provides the presentation of 20% to 40% of TSAs in the thymus [ 114 , 115 , 134 ], it can be suggested that the Treg pool of the thymic origins contains the same percent of TCRs specific to AIRE-dependent antigens. It should be noted that due to the formation of the pool of Treg lymphocytes, AIRE indirectly affects the formation of the peripheral repertoire of BCRs [ 156 , 157 ]. It was shown that AIRE deficit led to a condition when the pool of effector CD4 + lymphocytes accumulated numerous TCRs that normally belong to the Treg pool [ 156 , 158 ].…”
Section: The Role Of Aire In the Formation Of Tcr And Bcr Repertoiresmentioning
confidence: 99%
“…It was established that in patients with APECED syndrome or AIRE-deficient mice, the negative selection of self-reactive B-cells was impaired on the periphery, which is normally provided by an inhibiting influence of Treg lymphocytes [ 156 , 159 ]. These patients accumulate mature naïve self-reactive B-cells that produce a wide range of autoantibodies with low specificity to various AIRE-dependent antigens, which is manifested in the clinical picture of patients with APECED syndrome [ 156 , 157 , 159 ].…”
Section: The Role Of Aire In the Formation Of Tcr And Bcr Repertoiresmentioning
confidence: 99%